Novel low-delay scheme for parallel Turbo decoding - REN De-feng; GE Jian-hua; GONG Feng-kui; WANG Yong (Tongxin xuebao)
In order to decrease decoding delay because of the iterative and recursive computation in MAP class algo-rithms,a novel parallel decoding scheme was proposed.The key of the novel scheme was to design a novel collision-free（CF） interleaver.After the analysis of the CF criterion,the design criterion and an implementation approach of the CF in-terleaver based on the window were proposed by using the idea of the sliding window.The novel CF interleaver allowed extrinsic information immediately as priori information to start the next component decoding so as to decrease decoding delay.Finally,simulation results show the BER performance of novel parallel decoding scheme.